2011
DOI: 10.1111/j.1945-5100.2011.01203.x
|View full text |Cite
|
Sign up to set email alerts
|

Space radiation processing of sulfides and silicates in primitive solar systems materials: Comparative insights from in situ TEM ion irradiation experiments

Abstract: Abstract-Mineral grains that comprise dust particles in circumstellar, interstellar, and protostellar environments can potentially undergo amorphization and other solid-state transformations from exposure to energetic ions from space plasmas. The Fe-sulfide minerals troilite (FeS) and pyrrhotite (Fe 1)x S) are important known dust components, but their potential to undergo structural changes, including amorphization, from space radiation processing in dusty space environments has not been experimentally evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…Experiments reported in Wang et al [] indicate that olivine is more resistant than orthopyroxene to amorphization due to radiation damage. The same trend was reported in Christoffersen and Keller [], although the results were accurate within the experimental error. The results presented here suggest an explanation for these observations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Experiments reported in Wang et al [] indicate that olivine is more resistant than orthopyroxene to amorphization due to radiation damage. The same trend was reported in Christoffersen and Keller [], although the results were accurate within the experimental error. The results presented here suggest an explanation for these observations.…”
Section: Discussionsupporting
confidence: 89%
“…The particular focus is on comparison to existing radiation damage experiments performed on enstatite and olivine samples [ Christoffersen and Keller , ; Wang et al , ; Carrez et al , ]. Irradiation experiments using heavy ions by Christoffersen and Keller [] showed a similar critical radiation dose for amorphization in olivine and enstatite, although olivine was found to be slightly more resistant to amorphization. On the other hand, Wang et al [] found that olivine required about 4 times higher radiation dose than enstatite to get amorphized, suggesting olivine might be more radiation resistant.…”
Section: Introductionmentioning
confidence: 99%
“…The ion processing behavior of pyroxene relative to a wide range of other silicates has, however, been investigated under irradiation similar to the regime expected for the solar wind (Wang and Ewing 1992;Wang et al 1998a,b;Christoffersen and Keller 2011). These studies suggest that structures in which the Si-O tetrahedral sites are more polymerized, as in plagioclase, with a greater variety of interstitial sites, are generally much more susceptible to radiation-induced amorphization (Wang and Ewing 1992).…”
Section: Amorphization Featuresmentioning
confidence: 99%
“…Hence, the provided dataset seems only relevant for magnesian olivines, and not for all types of olivines. In particular, it should be noted that ion-beam irradiation data indicate that the irradiation resistance of forsterite (Wang et al 1998;Carrez et al 2002;Christoffersen and Keller 2012) is much higher than that of fayalite .…”
Section: (5) Maximum Rives Of Varied Orthosilicatesmentioning
confidence: 99%